Maintaining Work Life Balance Among Female Medical Staff Through Positive Work Environment: : Evidence from Malaysia - AHMAD ZAWAWI, AZLYN (Advances in Humanities and Contemporary Studies, 2023)
The concept of work-life balance is based on the notion that paid work and personal life should be seen as corresponding essentials of a full life. Work- life balance reflects a person's orientation across career and non-career life roles, and a conflict between work and life is seen as a mismatched between inter-role phenomenon. The need for work-life balance (WLB) has become even more pressing because of changes in the composition of the workforce. Longer working hours and after-hours connectivity not only negatively affect employees' lifestyle health but also limits their time available for non-work life. Women are more likely to spend more working hours than men are and the larger share of household work that is generally borne by women could cause this. A positive work climate leads to a strong emotional bond between organizational members, which in turn increases employees' engagement, commitment, loyalty and performance. If employees feel that the work environment is not safe, uncomfortable and unharmonious, it will cause discomfort, which may affect organizational performance. Organization need to take care of their employees by helping them maintaining a stable balance between their personal and professional life. This paper analyzed the relationship between a positive work environment (via supervisory support and flexible work arrangement) and the work-life balance of selected female medical staff in a hospital in Peninsular Malaysia. The findings of this study revealed that supervisory support and flexible work arrangements are important in helping employees developed a caring and helpful workplace.